Nitrogen-containing novolac-derived carbon beads as electrode material for supercapacitors. (June 2018) - Krüner, Benjamin; Schreiber, Anna; Tolosa, Aura; Quade, Antje; Badaczewski, Felix; Pfaff, Torben; Smarsly, Bernd M.; Presser, Volker
Abstract: We pyrolyzed and activated novolac beads in one single step with ammonia at different temperatures (750–950 °C), which leads to a highly porous carbon with nitrogen-doping. The chemical and physical properties were characterized and correlated with the electrochemical performance as supercapacitor electrodes. The average pore size varied at 0.6–1.4 nm dependent on the synthesis temperatures. Three different electrolytes (aqueous, organic, and an ionic liquid) were tested. The specific capacitance in a symmetrical supercapacitor reached up to 173 F g −1 and was strongly dependent on the porosity of the electrode material and the kind of electrolyte. We found that the presence of nitrogen enhanced the electrochemical performance stability and led to a high specific energy of 50 Wh·kg −1 using an ionic liquid as electrolyte. Graphical abstract: Image